2019
DOI: 10.1007/s40544-019-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective sugar-derived organic gelator for three different types of lubricant oils to improve tribological performance

Abstract: In this study, the gelling ability and lubrication performance of N-octadecyl-D-gluconamides (NOG) in liquid paraffin (LP), pentaerythritol oleate (PE-OA), and polyethylene glycol (PEG) oils were systemically investigated. The NOG, which could gelate the investigated oils, was successfully synthesized by a one-step method. The prepared gel lubricants were completely thermoreversible and exhibited improved thermal stability, according to the thermogravimetry analysis (TGA) reports. Rheological tests confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…25 These tribology properties indicated that BHTA has shown a similar effect on tribological performance with other reported LMWG, 22,25,90,91 and the resulting 150BS + BHTA lubricants can offer a better protection for friction pairs under different conditions. 22,26 Figure 8 shows scanning electron microscope (SEM) morphologies 25 of the wear surfaces lubricated by 150BS and 2% gel in 150BS. After magnifying the local scar images by 50 times and 500 times, respectively, we can see that the wear scar lubricated by blank 150BS is both larger in area and deeper in depth than 150BS with 2 wt % gel.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 These tribology properties indicated that BHTA has shown a similar effect on tribological performance with other reported LMWG, 22,25,90,91 and the resulting 150BS + BHTA lubricants can offer a better protection for friction pairs under different conditions. 22,26 Figure 8 shows scanning electron microscope (SEM) morphologies 25 of the wear surfaces lubricated by 150BS and 2% gel in 150BS. After magnifying the local scar images by 50 times and 500 times, respectively, we can see that the wear scar lubricated by blank 150BS is both larger in area and deeper in depth than 150BS with 2 wt % gel.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Recently, adding LMWG to a base lubricant oil has received special concern. The Mori group and Liu group have reported that several LMWG can gelate a variety of lubricating oils and the resulting gel lubricants could significantly reduce the friction and wear on the contact surface during sliding than that of the commonly used commercial base oil. …”
Section: Introductionmentioning
confidence: 99%
“…Friction and wear phenomena are common in mechanical industry, which always lead to tremendous energy loss and have a lot of disadvantageous effects on the mechanical system, eventually lower the production efficiency 1–3 . Lubricant oils, substances that can effectively reduce friction and wear, are widely used in this field for many superiorities compared with solid lubricants, such as long lubricating life, low work noise, and good heat dissipation performance 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Extensive research and experience in the past decades have shown that the most effective way to save energy and reduce wear were to apply lubricants, while solid lubrication and liquid lubrication are the main ways to use. Liquid lubrication (mainly oil) has the characteristics of high uidity and easy to form a stable oil lm between friction pairs, while solid lubricant (mainly grease) has better sealing performance and longer service life than the former [8][9] . In addition, the solid lubricant can adapt to high temperature, humidity, sea water and other harsh environments, enhance the anti-rust ability, reduce the maintenance time and effective reduce the production cost.…”
Section: Introductionmentioning
confidence: 99%